REMUNERAÇÃO DOCENTE NO ESTADO DE MATO GROSSO DO SUL FRENTE A AMPLIAÇÃO E A RESTRIÇÃO DE DIREITOS (2008 a 2022) - DANIELLI ARAUJO JARCEM (2023)
This research is part of the line of research in History, Policies and Education of the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul (PPGEDU/UFMS). It presents an excerpt from the research entitled: The effects of Brazilian Political Economy on the composition of basic education teacher remuneration, financed by the National Council for Scientific and Technological Development of Brazil, (CNPq). Its objective is to analyze the remuneration of education professionals in the state education network of Mato Grosso do Sul between two economic cycles: the first of expansion of public finances that expanded teaching rights in intersection with federal government policies (2008 to 2016); the second cycle, identified as fiscal austerity, which, on the contrary, restricted teaching rights. Thus, the first cycle is identified by the study of the legal mechanisms that provided increased teaching wages. The second cycle is characterized by the approval of State Constitutional Amendment nº 77/2017 in alignment with Constitutional Amendment nº 95/2016 approved in a national context. The analysis period covered the year 2008 as a result of the implementation of the Professional Salary Floor Law as a positive policy for the teaching category, until the year 2022. The research will be outlined using a qualitative approach, based on the study of documents produced by the movement organization and demands of teachers, as well as the bibliographical review on the subject of teacher remuneration and fiscal adjustment. It appears that the period of fiscal austerity, on a national scenario, had effects in the state of Mato Grosso do Sul regarding the change in the state's Jobs and Careers Plan (PCC), the breakdown of salary equality for teachers who have temporary contracts in the state network, as well as decreases in the salaries of these professionals. EC 77/2017 has been causing negative effects for the teaching category, which makes the valorization of this profession unfeasible.